RESPON PERTUMBUHAN DAN HASIL JAGUNG MANIS TERHADAP PUPUK KANDANG KOTORAN SAPI DAN KAPUR DOLOMIT PADA TANAH ALUVIAL - Maharani, Holitia; Sasli, Iwan; Santoso, Eddy (Fakultas Pertanian Universitas Tanjungpura, 2019)
This study aims to see the interaction between cow manure and dolomite lime on the growth and yield of sweet corn on tan on aluvial soil. Research conducted at the District Sibawek Mempawah Hulu Landak. This study uses a randomized block design (RAK) factorial design with two factors and three replications. The first factor is giving cow manure 3 levels: p1 (giving cow manure) 10,000kg/ha equivalent to 4 kg/bedengan, p2 (giving cow manure) 20,000kg/ha equivalent to 8 kg/bedengan, p3 (giving cow manure) 30,000kg/ha equivalent to 12 kg/bedengan and second factor giving dolomite lime with 3 levels: k1 (dolomite lime) 0.90 kg dolomite/ha equivalent to 0.36g/bedengan, k2 (dolomite lime) 1.26kg/ha equivalent to 0.50g/bedengan and k3(dolomite lime) 1.51kg of dolomite/ha equivalent to 0.60g/bedengan.Variables observed included plant height, flowering age, number of leaves, ear length of plant, ear diameter and ear weight of plant. The 5% BNJ test results that there are interactions on the administration of cow manure and dolomite lime on the cob variable, which is shown in the treatment of p2k2 ( 8kg cow manure / beds and 0,50 g dolomite lime / beds).